Differences in the Phenology of Harmonia axyridis (Coleoptera: Coccinellidae) and Native Coccinellids in Central Europe. Issue 1 (4th December 2018) - Honek, Alois; Martinkova, Zdenka; Roy, Helen E; Dixon, Anthony F G; Skuhrovec, Jiri; Pekár, Stano; Brabec, Marek
Abstract: Harmonia axyridis (Pallas), an invasive non-native species in central Europe, can outcompete other aphidophagous species. The distribution and abundance of H. axyridis vary depending on different host plants, and its effects on native coccinellid communities may change accordingly. The distribution and abundance of coccinellids in central Europe (50°N, 14°E) were investigated from 2010 to 2016. Coccinellids were counted at regular intervals on cereals ( Avena, Hordeum, and Triticum ), herbaceous plants ( Matricaria and Urtica ) and trees ( Acer, Betula, and Tilia ). Additionally, the occurrence over time of each species on these plants was assessed and used as an index of persistence. Across all years, the adults and larvae of H. axyridis were the dominant species of coccinellid on trees. However, H. axyridis was less abundant on herbaceous plants and cereals than on trees. Populations of native coccinellids and H. axyridis co-occurred on trees and persisted for the same length of time, while native coccinellids persisted longer than H. axyridis on herbaceous plants and cereals. Compared to 1976–1986, in the 2010s, the abundance of native species decreased on all plants by 50–70%. The presence of H. axyridis could be considered as a factor driving changes in the assemblages of native coccinellids.